Réponses

Meilleure réponse !
2014-09-17T22:19:03+02:00
Bonsoir
A = (2x-7)² - 49 
A = (2x-7)² - 7²        Identité remarquable a²-b² = (a-b)(a+b) 
A = (2x - 7 - 7)(2x - 7 + 7 )
A = (2x - 14)(2x) 

B = (3x-3)(2x+7)-(9x²-9)
B = (3x-3)(2x+7)- ( (3x)² - 3² )       identité remarquable a²-b² = (a-b)(a+b)
B = (3x-3)(2x+7) - ( 3x-3)(3x+3)   facteur commun  (3x-3) 
B = (3x-3)( 2x+7 - (3x+3)) 
B = (3x-3)( 2x+7 - 3x - 3)
B = 3x-3)(4-x) 

C = 4(1-6x)(7x-2) + 9(x-3)(7x-2)      
C = (4 - 24x)(7x-2) + (9x - 27)(7x - 2)
C = (7x-2)(4-24x+9x-27) 
C = 7x - 2)( -15x - 23) 

D = (5x-8)² - (2x+9)² 
D = (5x - 8 - 2x - 9)( 5x - 8 + 2x + 9)
D = (3x - 17)( 7x + 1) 
Bonne soirée